2020
DOI: 10.3892/etm.2020.8749
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA MIAT increases cell viability, migration, EMT and ECM production in age‑related cataracts by regulating the miR‑181a/CTGF/ERK signaling pathway

Abstract: Age-related cataract (ARC) is a common cause of blindness in elderly individuals. Long non-coding RNA (lncRNA) myocardial infarction associated transcript (MIAT) has been reported to participate in various biological processes in a number of diseases; however, the biological mechanism underlying MIAT during ARC is not completely understood. The expression levels of MIAT, microRNA (miR)-181a and connective tissue growth factor (CTGF) were measured by reverse transcription-quantitative PCR. The protein expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…These results suggest that CCN2 -derived circRNA (A) has a function in the regulation of ACAN mRNA expression specifically. Of note, this circRNA contains a miR-181-5p target in its 3′-UTR segment (Ling et al 2020 ), and our previous study clearly showed that exogenous miR-181a-5p drastically decreased the ACAN mRNA in HCS-2/8 cells, strongly suggesting their direct interaction (Sumiyoshi et al 2013 ). Therefore, to investigate the suppression mechanism of ACAN mRNA expression by knockdown of CCN2 -derived circRNA (A), a reporter gene assay was performed using a firefly luciferase reporter that contains a target sequence of miR-181-5p (Sumiyoshi et al 2013 ).…”
Section: Resultsmentioning
confidence: 81%
“…These results suggest that CCN2 -derived circRNA (A) has a function in the regulation of ACAN mRNA expression specifically. Of note, this circRNA contains a miR-181-5p target in its 3′-UTR segment (Ling et al 2020 ), and our previous study clearly showed that exogenous miR-181a-5p drastically decreased the ACAN mRNA in HCS-2/8 cells, strongly suggesting their direct interaction (Sumiyoshi et al 2013 ). Therefore, to investigate the suppression mechanism of ACAN mRNA expression by knockdown of CCN2 -derived circRNA (A), a reporter gene assay was performed using a firefly luciferase reporter that contains a target sequence of miR-181-5p (Sumiyoshi et al 2013 ).…”
Section: Resultsmentioning
confidence: 81%
“…To explore lncRNAs in the physiopathological mechanism of cataracts, Shen et al compared the lens of cataract patients to that of normal people and found that lncRNA MIAT is a speci c biomarker of cataract, and lncRNA MIAT participates in regulating the function of HLECs through miR-150-5p/Akt, which has an impact on cell viability, cell proliferation, and apoptosis [51] . Studies have also shown that MIAT increased cell viability, migration, epithelial-mesenchymal transition (EMT), and extracellular matrix production during ARC by activating the extracellular signal-regulated kinase signaling pathway via the miR-181a/connective tissue growth factor axis [52] . Therefore, the novel regulatory network identi ed in this study may serve as a therapeutic target for ARC and provide a theoretical basis for the mechanism underlying ARC development [52] .…”
Section: Miatmentioning
confidence: 99%
“…Studies have also shown that MIAT increased cell viability, migration, epithelial-mesenchymal transition (EMT), and extracellular matrix production during ARC by activating the extracellular signal-regulated kinase signaling pathway via the miR-181a/connective tissue growth factor axis [52] . Therefore, the novel regulatory network identi ed in this study may serve as a therapeutic target for ARC and provide a theoretical basis for the mechanism underlying ARC development [52] .…”
Section: Miatmentioning
confidence: 99%
“…Age-related cataract (ARC) is the leading cause of world blindness, which causes ~50% blindness worldwide 148 . Few circRNA has been identified in cataract.…”
Section: A-modified Circrna Associated With Pathophysiological Processesmentioning
confidence: 99%